Cocoa Cultivation and Its Development Prospects in Southeast Sulawesi in Facing the Global Market - Imran Imran (Journal of Agriculture, Agribusiness, Welfare, Technology, Humanity, Environment, Social, and Economy, 2025)
Cocoa is one of Indonesia’s leading commodities that significantly contributes to the national economy, particularly in the Southeast Sulawesi region. This area is known as one of the largest cocoa-producing centers in Indonesia, with vast potential for further development. This study aims to examine the current state of cocoa cultivation in Southeast Sulawesi and its prospects in facing the challenges of the global market through a literature review approach. The study highlights various aspects, including agroecological conditions, cultivation techniques, productivity levels, and challenges in the supply chain and marketing. The findings indicate that cocoa development in Southeast Sulawesi has great potential but still faces several issues, such as poor seed quality, pest and disease attacks, and limited post-harvest technological innovation. Furthermore, environmental sustainability and product certification have become major requirements in global trade. Strengthening farmers’ capacity, implementing sustainable agricultural practices, and providing strong support from both local and national governments are key factors in enhancing the competitiveness of Southeast Sulawesi cocoa in international markets. With proper management strategies, cocoa can become a highly competitive leading commodity that contributes to improving local community welfare.